Intensity and Prevalence of Ectoparasites in Carp in Cirata Reservoir KJA, Cianjur Regency, West Java - Sri Lusi Mulyani; Mulyani, Yuniar; Rochima, Emma; Roffi Grandiosa (Grouper, 2025)
One of the problems that arise in fish farming is the occurrence of disease attacks that can cause losses to farmers. Parasites that are classified as ectoparasites themselves usually live outside the host. The purpose of this study was to analyze the level of intensity and prevalence of ectoparasites in goldfish in Floating Net Cages (KJA). The study used a survey method, fish samples were taken using purposive sampling method. The results showed that the highest intensity value at station 1 was Tricodina sp. 7 ind/head, station 2 was Ichthyophtirius multifilis which was 2.5 ind/head, station 3 was Dactylogyrus sp. which was 2.75 ind/head with a low-medium category. The lowest intensity value is station 1 Lernea sp. and Ergasilus sp. 1 ind/head, station 2 namely Vorticella sp. and Gyrodactylus sp. namely 1 ind/head, station 3 Chilodonella sp. and Gyrodactylogyrus sp. namely 1 ind/head with a low category. The prevalence value of station 1 is Dactylogyrus sp. 20%, station 2 Dactylogyrus sp. 20.00%, station 3 Dactylogyrus sp. 20.00% with frequent category. The lowest station 1 Lernea sp. 3.33%, Tricodina sp. 3.33%, Ergasilus sp. 3.33%, and Ichthyophtirius multifilis 3.33%. Station 2 Chilodonella sp. 3.33%, and Vorticella sp. 3.33%. Station 3 Gyrodactylus sp. 3.33% with the category sometimes.